Wokół „Legend tęsknoty” Bolesława Leśmiana - Filipek, Artur (Colloquia Litteraria, 2023)
Bolesław Leśmian enjoy unflagging popularity this days. Because of that, I tried to revalue Legends of longing, which appeared in researches as a rader modest, early works than valid mile stone in writing practise of Leśmian. To do so, I’ve read them mostly in hermeneutical way.